Efficient communication in organizations - Vaccari, Federico (Fondazione Eni Enrico Mattei, 2022)
Organizations design their communication structures to improve decision-making while limiting wasteful influence activities. An efficient communication protocol grants completeinformation payoffs to all organization members, thereby overcoming asymmetric information problems at no cost. This paper characterizes efficient protocols assuming that: (i) some agents within the organization have the knowledge required for optimal decision-making; (ii) both the organization and consulted agents incur losses proportional to the exerted influence activities; and (iii) informed agents can discuss their strategies before being consulted. Under these assumptions,
10419/267504
Keywords: Graue Literatur; Information; Communication; Organizations; Efficiency; Costly Talk